Scleredema associated with Sjögren's syndrome - João Alves; Tiago Judas; Tiago Ferreira; Diogo Matos; Elvira Bártolo (Sociedade Brasileira de Dermatologia, 2015)
AbstractScleredema adultorum of Buschke is a rare disorder characterized by diffuse swelling and non-pitting induration of the skin usually involving the face, neck, arms and upper trunk. It has been associated with previous infectious diseases, diabetes, paraproteinemia and, more rarely, malignant neoplasms or autoimmune disorders. We report the case of a 30-year-old man who presented with a 2-year history of scleredema. Further investigation led to the diagnosis of primary Sjögren's syndrome. The association between scleredema and autoimmune disorders has been rarely seen. To our knowledge, there are no other reports describing the association between primary Sjögren's syndrome and scleredema adultorum of Buschke.